NEW MODERN METHODS IN TEACHING ENGLISH (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In many parts of the world, there is a growing interest in modern methods of teaching English, the question of how to do it - how the curriculum, subject, topic and methodology should differ from the previously developed familiar norms gives birth. Much has been written on traditional English teaching and there is a growing body of knowledge about modern methods of teaching English. Many books and articles have been written to draw attention to this topic today. The use of innovations and new pedagogical technologies is yielding good results. This article discusses several methods and types of teaching.